Studies on the Australian stick insects (Phasmida), including a checklist of species and bibliography - Brock, Paul D.; Hasenpusch, Jack (Zootaxa, 2007)
The Australian phasmid fauna has been revised prior to publication of a field guide by the same authors. Six new genera are described: Austrosipyloidea Brock & Hasenpusch, Cornicandovia Hasenpusch & Brock, Davidrentzia Brock & Hasenpusch, Micropodacanthus Brock & Hasenpusch, Paratropidoderus Brock & Hasenpusch and Spinosipyloidea Hasenpusch & Brock. Sixteen new species from various parts of Australia are described and figured: Candovia robinsoni Brock & Hasenpusch, Rhamphosipyloidea palumensis Hasenpusch & Brock, Scionecra milledgei Hasenpusch & Brock, Sipyloidea brevicerci Hasenpusch & Brock, Sipyloidea garradungensis Hasenpusch & Brock, Sipyloidea larryi Hasenpusch & Brock, Sipyloidea lewisensis Hasenpusch & Brock, Sipyloidea rentzi Brock & Hasenpusch, Sipyloidea whitei Brock & Hasenpusch, Spinosipyloidea doddi Hasenpusch & Brock [all Necrosciinae], Pachymorpha spinosa Brock & Hasenpusch [Pachymorphinae], Davidrentzia valida Brock & Hasenpusch [Platycraninae], Micropodacanthus mouldsi Brock & Hasenpusch, Micropodacanthus sztrakai Brock & Hasenpusch, Paratropidoderus spinosus Brock & Hasenpusch and Podacanthus keyi Brock & Hasenpusch [Tropidoderinae].        A number of new combinations are proposed, new synonyms and incorrect synonymy corrected following detailed examination of type and other material: 1. (Lonchodinae): Austrocarausius Brock, 2000: Carausius macerrimus Brunner, 1907 is a new synonym of Austrocarausius nigropunctatus (Kirby, 1896). Denhama Werner, 1912: D. austrocarinata (Otte & Brock, 2005), D. longiceps (Brunner, 1907), D. striata (Sjöstedt, 1918) and D. eutrachelia (Westwood, 1859) are transferred from Hyrtacus Stål, 1875, the latter species also removed from synonymy with Hyrtacus coenosa (Gray, 1833). D. gracilis (Sjöstedt, 1918), a former Marcenia species, is also transferred. Hyrtacus Stål, 1875 (= Marcenia Sjöstedt, 1918 syn. n.): H. caurus (Tepper, 1905) comb. n. transferred from Lonchodes Gray, 1835 (three new synonyms also reported for this species: Bacillus peristhenellus Tepper, 1905, Hyrtacus cunctatrix (Sjöstedt, 1918) and Hyrtacus nigrogranulosus Sjöstedt, 1918). Marcenia frenchi (Wood-Mason, 1877) is a new synonym of Hyrtacus tuberculatus Stål, 1875. 2. (Necrosciinae): Austrosipyloidea Brock & Hasenpusch, gen. n.: A. carterus (Westwood, 1859) comb. n., transferred from Sipyloidea Brunner, 1893 (= Sipyloidea filiformis Redtenbacher, 1908 syn. n.). Candovia Stål, 1875 is removed from synonymy with Hyrtacus, along with the type species, C. coenosa. This has resulted in all former Australian species placed in Parasipyloidea Redtenbacher, 1908 being transferred to Candovia i.e. C. aberrata (Brunner, 1907) comb. n., C. annulata (Brunner, 1907) comb. n., C. granulosa (Brunner, 1907) comb. n., C. pallida (Sjöstedt, 1918), comb. n., C. spurcata (Brunner, 1907) comb. n. and C. strumosa (Redtenbacher, 1908) comb. n. In addition, C. evoneobertii (Zompro & Adis, 2001) comb. n. and C. peridromes (Westwood, 1859) comb. n. (including its new synonyms Clitarchus longipes Brunner, 1907, Bacunculus tener Brunner, 1907 and E. cercatus (Redtenbacher, 1908)) are transferred from Echetlus Stål, 1875. Cornicandovia Hasenpusch & Brock gen n.: C. australica (Redtenbacher, 1908) comb. n. Sipyloidea Brunner, 1893: S. bella (Tepper, 1905) comb. n. (new synonym S. ovabdita Rentz & John, 1987) is transferred from Necroscia Serville, 1838, S. caeca Sjöstedt, 1918 rev. stat., is removed from synonymy with Sipyloidea carterus (Westwood, 1859).  Rhamphosipyloidea Redtenbacher, 1908: R. queenslandica (Sjöstedt, 1918) comb. n. is transferred from Sipyloidea, also removed from synonymy with carterus. 3. (Pachymorphinae): Pachymorpha Gray, 1835: P. pasithoe (Westwood, 1859) is a new synonym of P. simplicipes Serville, 1838. 4. (Eurycanthinae). Eurycantha Boisduval, 1835: E. sifia (Westwood, 1859) is a new synonym of E. calcarata Lucas, 1870. 5. (Phasmatinae): Vetilia Stål, 1875 is a new synonym of Acrophylla Gray, 1835, resulting in the transfer of these species to Acrophylla: A. enceladus (Gray, 1835) comb. n. and A. thoon (Stål, 1875) comb. n. Vetilia ligia Redtenbacher, 1908 is a new synonym of Acrophylla wuelfingi Redtenbacher, 1908. A. paula (Tepper, 1905) and A. aliena Redtenbacher, 1908 are new synonyms of A. nubilosa Tepper, 1905. A. caprella (Westwood, 1859) comb. n. is transferred from Ctenomorpha Gray, 1833. Anchiale Stål, 1875 (= Ctenomorphodes Karny, 1923 syn. n.), resulting in the transfer of  A. briareus (Gray, 1834) comb. n. and A. tessulata (Gray, 1835) which is renamed Anchiale austrotessulata name nov., as tessulata Gray is preoccupied by Anchiale tessulata (Goeze, 1778). Austroclonistria Redtenbacher, 1908 is a new synonym of Arphax Stål, 1875, as A. serrulataa Redtenbacher, 1908) is a new synonym of Arphax dolomedes (Westwood, 1859). Ctenomorpha Gray, 1833: Paractenomorpha macrotegmus (Tepper, 1887) is confirmed as a synonym of Ctenomorpha marginipennis Gray, 1833. Hermarchus Stål, 1875: H. polynesicus Redtenbacher, 1908 is a new synonym of H. insignis (Kaup, 1871). Paronchestus Redtenbacher, 1908: P. cornutus (Tepper, 1905) comb. n. is transferred from Acrophylla Gray, 1835 and P. pasimachus (Westwood, 1859) from Onchestus Stål, 1875. 6. (Platycraninae): Megacrania batesii (Kirby, 1896) is removed from synonymy with Megacrania alpheus (Westwood, 1859). 7. (Tropidoderinae): Didymuria Kirby 1904: D. virginea Stål, 1875 is removed from synonymy with D. violescens (Leach, 1814). Lysicles Stål, 1877: L. periphanes (Westwood, 1859) comb. n. is transferred from Echetlus Stål, 1875. Tropidoderus Gray 1835: T. michaelseni Werner, 1912 is removed from synonymy with T. childrenii (Gray, 1833). 8. (Xeroderinae): Cooktownia Sjöstedt, 1918 becomes a new synonym of Xeroderus Gray, 1835, as Cooktownia plana Sjöstedt, 1918 is a new synonym of Xeroderus kirbii Gray, 1835.Lectotypes are designated for Clitarchus longipes Brunner, 1907, Sipyloidea filiformis Redtenbacher, 1908 and Vetilia ligula Redtenbacher, 1908.As a result of this work, there are now 104 Australian species (+ 1 subspecies) and in order to facilitate further research on these insects, an updated checklist is provided, also a detailed bibliography.